2021
DOI: 10.3390/ijerph18126398
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Youth Physical Activity Promotion Model during the COVID-19 Pandemic, with Partial Least Squares Second-Order Latent Constructs

Abstract: We tested the Youth Physical Activity Promotion (YPAP) framework on Romanian students in order to identify actionable determinants to support participation in physical activity. Our sample consisted of 665 responses to an online survey, with participants aged 18–23 (mean = 19 years); 70% were women. We used the partial least squares algorithm to estimate the relationships between students’ behavior and possible predictors during the COVID-19 pandemic. Our results indicate that all the theoretical dimensions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Applying the Youth Physical Activity Promotion (YPAP) framework showed that ability and self-worth strongly influence physical activity in Romanian students, alongside other predisposing, enabling, and reinforcing factors [54].…”
Section: Physical Activitymentioning
confidence: 99%
“…Applying the Youth Physical Activity Promotion (YPAP) framework showed that ability and self-worth strongly influence physical activity in Romanian students, alongside other predisposing, enabling, and reinforcing factors [54].…”
Section: Physical Activitymentioning
confidence: 99%
“…[10][11][12][13] The comprehensive Youth Physical Activity Promotion (YPAP) model 14 has been applied to understand PA among university students during the pandemic. 15 The model highlights the interaction of predisposing, enabling, and reinforcing factors influencing PA.…”
Section: Introductionmentioning
confidence: 99%
“…which assess the degree of control one has on PA with respect to motivations and beliefs. 15 The strict societal measures under the pandemic might have affected both the psychological state (motivation, attitudes, and mental health) and decreased both the reinforcing social factors such as peers and role models and the enabling environmental conditions, with subsequent effects on students' perceived behavioral control of PA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations